PELATIHAN PEMANFAATAN APLIKASI ZOTERO DALAM UPAYA MENGHINDARI PLAGIARISME PENULISAN KARYA ILMIAH DIKALANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS GRAHA NUSANTARA - Harahap, Adek Nilasari; Dalilah, Nur; Lubis, Susi Sulastri; Sari, Siti Meutia (Jurnal Pengabdian Masyarakat, 2023)
For a variety of urgent reasons, opportunities to cheat in order to conduct scientific work continue to be developed. As a result, academics, particularly undergraduates, are prone to plagiarism. It is possible to teach pupils how to utilize the Zotero application. The goal is to improve pupils' writing skills by using the Zotero application. The service implementation team's strategy includes socializing and training based on their area of competence. For one day in a row, intriguing activities are carried out. The training method is implemented in stages, beginning with planning and concluding with evaluation.More instructions are offered, beginning with the generation of material and progressing to practical tasks. The course outcomes reveal that students who participated in the training increased their skills using the Zotero program. This is evidenced by the evaluation findings, which revealed that 85% of the students enrolled in the program were becoming more proficient in handling references and selecting the appropriate references to include in scientific articles.